(untitled) (International Journal of Medical and Surgical Sciences, 2023)
Introduction: Cardiovascular dysfunction is the first cause of death in patients with chronic kidney disease. Methods: Observational, longitudinal and prospective study, which included 58 patients with functioning renal transplant who were studied different echocardiographic variables, before and six months after the closure of the arteriovenous fistula. Results: The average age was 46.62 years and the most frequent was male 30 (51.72%). The flow of angioaccesses at the wrist level was demonstrated in 28 patients (45.9%) with evidence of regression of mean pulmonary artery pressure from 25.56 to 19.58 mmHg (p=0.002), more connoted for those of intermediate flow; 14. Also, the area of tricuspid insufficiency was greater for that group; from 3.15 to 1.96 cm2 (p=0.001). The pattern of mild dysfunction was observed in 38 patients (62.3%) prior to closure. Subsequent to this 27; (51.9%), exhibited minimal valvular insufficiency and 9 individuals (14.9%) did not show any degree of valvular dysfunction. Conclusions: Closure of the arteriovenous fistula in patients with functioning renal transplantation contributed to decrease the risk of pulmonary hypertension and progression of tricuspid valve dysfunction.